습성 나이관련황반변성에서 항혈관내피성장인자의 유효성과 안전성: 네트워크 메타분석 - 강민주(Min Joo Kang), 신상진(Sang Jin Shin), 서재경(Jae Kyung Suh), 조송희(Songhee Cho), 최하진(Hajin Tchoe), 양장미(Jangmi Yang), 지동현(Donghyun Jee) (Daihan angwa haghoi jabji, 2019)
목적: 나이관련황반변성환자의 치료에 쓰이는 베바시주맙, 라니비주맙 및 애플리버셉트의 유리체내 주입술의 유효성과 안전성을 메타분석을 통하여 비교하고자 하였다. 대상과 방법: 연구 목적에 부합하는 최근의 고품질의 체계적인 검토(Canadian Agency for Drug Technology in Health 2016)를 선정하였고, 여기에서 확인된 13건의 임상 시험에 3건의 무작위 임상 시험을 추가하여 메타분석 및 네트워크 메타분석을 시행하였다. 유효성 결과 지표로는 1) 시력의 평균 향상, 2) 시력 개선을 경험한 환자의 비율, 3) 시력이 악화된 환자의 비율을 파악하였고, 안전성 결과에는 전신 이상 반응 및 안구 관련 이상 반응을 분석하였다. 결과: 항혈관내피성장인자 간의 유효성 결과에는 유의한 차이가 없었다. 라니비주맙 대 베바시주맙의 평균 최대교정시력의 차이는 0.33 (95% confidence interval [CI], -1.29, 1.95)이었고 15글자 이상의 시력 증가에서는 라니비주맙 대 애플리버셉트의 위험도(odds ratio, OR)는 1.02 (95% CI, 0.80, 1.30)였다. 또한 동맥 혈전 색전증의 발생을 제외하고는 안전성 결과에 유의한 차이가 없었다(라니비주맙 대 베바시주맙, OR, 2.15; 95% CI, 1.04, 4.41). 결론: 나이관련황반변성에서의 항혈관내피성장인자의 유효성은 유의한 차이를 보이지 않았고, 안전성은 동맥 혈전 색전증 증상을 제외하고는 유의미한 차이가 없었다. Purpose: To compare the efficacy and safety of intravitreal injections of bevacizumab, ranibizumab, and aflibercept for the treatment of new patients with age-related macular degeneration (AMD). Methods: We conducted an update of the most recent and high quality systematic reviews (Canadian Agency for Drug Technology in Health [CADTH] 2016). Three randomized clinical trials were added to 13 trials identified from the CADTH report. The efficacy outcomes were 1) average improvement in visual acuity, 2) proportion of patients who experienced an improvement in vision (an increase in best-corrected visual acuity (BCVA) of ≥ 15 on Early Treatment Diabetic Retinopathy Study [ETDRS] letters), and 3) proportion of patients who experienced worsening of vision (decrease in BCVA of ≥ 15 ETDRS letters). In addition, safety outcomes included systemic adverse events and ocular-related adverse events. To analyze the outcomes of 16 randomized controlled trials, we conducted meta-analyses on the outcome measures. Results: There was no significant difference in efficacy outcomes among anti-vascular endothelial growth factor (anti-VEGF) drugs. The mean difference in BCVA between ranibizumab and bevacizumab was 0.33 (95% confidence interval [CI]: -1.29, 1.95), and the odds ratio (OR) for a vision gain in the BCVA of ≥ 15 ETDRS letters for the ranibizumab versus aflibercept treatment was 1.02 (95% CI: 0.80, 1.30). There was also no significant difference in safety outcomes, except in terms of arterial thromboembolic events (ranibizumab vs. bevacizumab; OR: 2.15; 95% CI: 1.04, 4.41). Conclusions: The efficacy of anti-VEGF drugs for AMD patients was not significantly different. The safety of the drugs was also not significantly different, except in terms of arterial thromboembolic events. KCI Citation Count: 0